Circular RNA profiling provides insights into their subcellular distribution and molecular characteristics in HepG2 cells. Issue 2 (1st February 2019) - Zhang, Ju; Zhang, Xiuli; Li, Cuidan; Yue, Liya; Ding, Nan; Riordan, Tim; Yang, Li; Li, Yang; Jen, Charles; Lin, Sen; Zhou, Dongsheng; Chen, Fei
ABSTRACT: Circular RNA (circRNA) is a novel RNA molecule that has become a research focus recently. Although some research indicated that the circRNAs in different subcellular compartments could execute different regulatory functions, a panoramic analysis of the subcellular distribution and the transport mechanism of circRNA is still required. In this study, we comprehensively analyzed the subcellular distribution/characteristics and the transport mechanism, through systemically investigating the circRNA profiles among the subcellular fractions of HepG2 cell (nucleus, cytoplasm, mitochondria, ribosome, cytosol and exosome). CircRNAs were widely distributed among the subcellular fractions except in the mitochondria, with differences in the subcellular distribution/characteristics in terms of classification, length, GC content, alternative circularization and parental gene function. Further analysis indicated this might be due to the selective transportation mediated by the transport-related RNA binding proteins (RBPs). The circRNAs may follow the same transportation mechanism of linear RNAs, in which the RBPs specially recognize/transport the RNAs with the corresponding binding motifs. Interestingly, we found that the exosome could selectively package the circRNAs containing the purine-rich 5ʹ-GMWGVWGRAG-3ʹ motif, with the characteristic of 'garbage dumping' and 'intercellular signaling' functions. Besides, although we observed numerous circRNAs enriched in the ribosome, we did not reliably identify any unique-peptides from circRNAs using 3D-LC-MS/MS strategy. This suggests that circRNAs rarely function as translation templates in vivo like lincRNA. Our findings not only indicates the differential distributions/characteristics among the subcellular fractions, but also reveals the possible transportation mechanism. This provides an improved understanding of the life history and molecular behavior of circRNA in cells.